13n-6=33

Simple and best practice solution for 13n-6=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13n-6=33 equation:


Simplifying
13n + -6 = 33

Reorder the terms:
-6 + 13n = 33

Solving
-6 + 13n = 33

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 13n = 33 + 6

Combine like terms: -6 + 6 = 0
0 + 13n = 33 + 6
13n = 33 + 6

Combine like terms: 33 + 6 = 39
13n = 39

Divide each side by '13'.
n = 3

Simplifying
n = 3

See similar equations:

| 5x+8+4x=.10 | | -2+42=4x | | (-y+5.3)+(7.2-9)=6.2y+n | | X/5=-9/15 | | 11y-7=48 | | -4(2t+2)=-48 | | 10(b-2)=40 | | 5x+38=2x+14 | | x^2-1.2x-0.64=0 | | 4(f-6)=4 | | -4+4x+2x=2 | | T*4-8=9 | | 15-(5m+3)=4+4m-19 | | 10(s-10)=-205 | | n^2-3n-49=0 | | (x^2/12)^6 | | (^6x^2/12) | | (n+2)(n-5)=39 | | 4=.3x+2x+6 | | 7(4s+5)=91 | | 10+8=78 | | 6(4+x)=54 | | 2(2l+5)=26 | | 8x-10=2x+80 | | 5n+6+7n=18 | | ln(5x-1)=ln(3x+2) | | 3(a-2)=63 | | -x+5+5x=-43 | | .02(.05c+.3)=.03c-.07(.3-.1c) | | p+12-6p=-8-7p | | 25S=3s^2+28 | | (ln(x)-5)*(x+6)=0 |

Equations solver categories